Correlation of Species Gastropods and the Parameters of Physical and Chemical Parameters of Water in the Mangetan River Canal of Kraton Village Sidoarjo - Siswansyah, Ravianda Putra Pratama; Kuntjoro, Sunu (LenteraBio : Berkala Ilmiah Biologi, 2023)
Sidoarjo Regency has river waters that support metropolitan cities like Surabaya. The many functions of rivers must also be balanced with their management in maintaining water quality so that it maintained. This study aimed to identify the species of freshwater gastropods, analyze the quality of waters, and analyze the correlation between the species of gastropods with the physical-chemical parameters of waters. This was observational reseach for sampling gastropods and measuring physico-chemical parameters. The research procedure consisted of field observations, location determination, gastropod sampling, and measurement of physico-chemical parameters and identification of gastropods. Data analysis was carried out in quantitative descriptive manner, identification based on morphological characteristics, and statistically using the Bivariate Pearson correlation test. Ten species of gastropods were found in Mangetan River Kanal Kraton Village belonging to 4 families. Water quality based on measurements of physical-chemical parameters is still in accordance with predetermined quality standards with brightness values ??of 25-57 cm and BOD ranging from 0.63-1.99 mg/L. There is a correlation between the types of gastropods and the physical-chemical parameters of water, which obtained the highest value of 0.964 in the species Thiara scabra with BOD and 0.942 in the species Pomacea canaliculata with temperature.